I am human : a book of empathy - Verde, Susan; Reynolds, Peter H. 1961- (Peter Hamilton) (New York : Abrams Books for Young Readers, 2018)
A child recognizes his own humanity, his capacity for doing harm and being harmed, his ability to feel joy and sadness, and his belief in hope and promise to keep learning.
Keywords: Empathy -- Fiction; Compassion -- Fiction; Conduct of life -- Fiction